A Comparative Analysis of Artificial Neural Network and Deep Learning Techniques in Heart Disease (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of Computers has made the drastic change in the lifestyle of human beings, by making them dependantto solvemany complex applications which was unable to solve him previously. There are many real time applications which needs the joint interaction of human &machine to obtainthe results in fruitful manner. The Artificial Neural Network which is based on the concept of biological brain plays a major role in this, but still suffers from many limitations. To overcome this, a new approach called Deep Learning, based on same human biological systemslike Artificial Neural Network, came into existence to find the best solution in the field of medical science. The main aim of this papers is to review the comparative analysis ofthese two techniques being used in the detection of Heart Disease.